Fate of engineered nanomaterials at the human epithelial lung tissue barrier in vitro after single and repeated exposures - Lehner, Roman; Zanoni, Ilaria; Banuscher, Anne; Costa, Anna Luisa; Rothen-Rutishauser, Barbara (Frontiers in Toxicology, 2022)
The understanding of the engineered nanomaterials (NMs) potential interaction with tissue barriers is important to predict their accumulation in cells. Herein, the fate, e.g. cellular uptake/adsorption at the cell membrane and translocation, of NMs with different physico-chemical properties across an A549 lung epithelial tissue barrier, cultured on permeable transwell inserts, were evaluated. We assessed the fate of five different NMs, known to be partially soluble, bio-persistent passive and bio-persistent active. Single exposure measurements using 100 µg/mL were performed for barium sulfate (BaSO4), cerium dioxide (CeO2), titanium dioxide (TiO2) and zinc oxide (ZnO) NMs, and non-nanosized crystalline silica (DQ12). Elemental distribution of the materials in different compartments was measured after 24 and 80 h, e.g. apical, apical wash, intracellular and basal, using inductively coupled plasma optical emission spectrometry. BaSO4, CeO2, and TiO2 were mainly detected in the apical and apical wash fraction, whereas for ZnO a significant fraction was detected in the basal compartment. For DQ12 the major fraction was found intracellularly. The content in the cellular fraction decreased from 24 h to 80 h incubation for all materials. Repeated exposure measurements were performed exposing the cells on 4 subsequent days to 25 µg/mL. After 80 h BaSO4, CeO2, and TiO2 NMs were again mainly detected in the apical fraction, ZnO NMs in the apical and basal fraction, while for DQ12 a significant concentration was measured in the cell fraction. Interestingly the cellular fraction was in a similar range for both exposure scenarios with one exception, i.e. ZnO NMs, suggesting a potential different behavior for this material under single exposure and repeated exposure conditions. However, we observed for all the NMs, a decrease of the amount detected in the cellular fraction within time, indicating NMs loss by cell division, exocytosis and / or possible dissolution in lysosomes. Overall, the distribution of NMs in the compartments investigated depends on their composition, as for inert and stable NMs the major fraction was detected in the apical and apical wash fraction, whereas for partially soluble NMs apical and basal fractions were almost similar and DQ12 could mainly be found in the cellular fraction.